Resistance of anammox granular sludge to copper nanoparticles and oxytetracycline and restoration of performance. (July 2020) - Cheng, Ya-Fei; Li, Gui-Feng; Ma, Wen-Jie; Xue, Yuan; Liu, Qi; Zhang, Zheng-Zhe; Jin, Ren-Cun
Highlights: Better resistance and resilience were observed in unacclimated anammox granular sludge. Anammox system was significantly suppressed by the addition of high level Cu NPs and OTC. Dominant bacteria and functional genes coincide with each other. The presence of ARGs improved the resistance of anammox sludge to Cu NPs and OTC. Abstract: Nanoparticles and antibiotics, the two most frequently detected emerging pollutants from different wastewater sources, are eventually discharged into wastewater treatment plants. In this study, the widely used materials CuNPs and oxytetracycline (OTC) were selected as target pollutants to investigate their joint effects on anaerobic ammonium oxidation (anammox). The results indicated that the environmental concentration slightly inhibited the performance of the reactors, while the performance rapidly deteriorated within a week under high-level combined shocks (5.0 mg L −1 CuNPs and 2.0 mg L −1 OTC). After the second shock (2.5 mg L −1 CuNPs and 2.0 mg L −1 OTC), the resistance of anammox bacteria was enhanced, with an elevated relative abundance of Candidatus Kuenenia and absolute abundance of hzs A, nir S, and hdh . Moreover, the extracellular polymeric substance (EPS) content and specific anammox activity (SAA) showed corresponding changes. Improved sludge resistance was observed with increasing CuNP and OTC doses, which accelerated the recovery of performance.